Influencing factors of hospitalization costs for intensive rehabilitation in patients with post-stroke disorder of consciousness - Yu, Miao; Huang, Zhongmou; Yang, Yansui; Wang, Yulin; Ren, Hai; Tang, Shilan (Frontiers in Public Health, 2025)
ObjectiveIn China, patients requiring intensive rehabilitation often face a gap between acute treatment and sub-acute rehabilitation. This study evaluates the composition and determinants of post-acute hospitalization costs in stroke patients with disorders of consciousness (DoC).MethodsData from 133 stroke patients with DoC who underwent inpatient rehabilitation at a tertiary hospital from 2015 to 2020 were collected, including demographic characteristics, clinical features, and hospitalization costs. Descriptive statistical analysis and univariate analysis were performed, followed by path analysis and Bootstrap mediation tests to explore factors influencing hospitalization costs.ResultsThe median hospitalization costs were 56,860.80. Rehabilitation costs accounted for the largest proportion of total hospitalization costs (36.55%). Direct factors influencing total costs included payment method, admission to the intensive care unit (ICU), pulmonary infection, and length of stay (LOS) (p < 0.05). The effect sizes ranked in descending order were LOS, ICU experience, payment method, and pulmonary infection. Bootstrap mediation tests revealed significant mediation effects (p < 0.05) of payment method, occupation, patient origin, hypertension, ICU experience, and death on total costs, indicating that these factors indirectly influenced costs by affecting LOS.ConclusionGreater attention should be given to meeting the rehabilitation needs of patients by expanding resources for intensive rehabilitation and ensuring continuous rehabilitation services. Comprehensive and effective measures should be implemented to address cost-influencing factors early, without compromising the quality of care.